Design, synthesis, and photosensitive performance of polymethacrylate‐positive photoresist‐bearing o‐nitrobenzyl group. Issue 13 (4th December 2014) - Guo, Lingxiang; Guan, Jing; Zhao, Xiaofang; Lin, Baoping; Yang, Hong
ABSTRACT Novel polymethacrylate‐positive photoresist‐bearing o‐nitrobenzyl group was described herein. The matrix polymer (PCHIBNB) was synthesized by copolymerization of cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBMA), and o‐nitrobenzyl methacrylate (NBMA) via reversible addition fragmentation chain transfer (RAFT) polymerization method. After UV irradiation, the o‐nitrobenzyl groups of PCHIBNB were photocleaved and the resulting carboxyl groups were highly alkali‐soluble, so that the matrix polymer could be etched by mild alkali solution with no requirements of photosensitizers or photoacid generators. PCHIBNB was characterized by Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1H‐NMR) spectroscopy, and gel permeation chromatography (GPC). The photocleavable behaviors of PCHIBNB were determined by FTIR, 1H‐NMR, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) analysis. The resist formulated with this polymer and cast in tetrahydrofuran (THF) solution showed 10 μm × 10 μm square pattern using a mercury–xenon lamp in a contact printing mode and tetramethyl‐ammonium hydroxide aqueous solution as a developer. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41733.